Utilization of antenatal care services and factors affecting antenatal care visits in Pokhara sub-metropolitan city - Paudel, Sabita; Paudel, Tarun; Sanjel, Seshananda (Journal of Karnali Academy of Health Sciences, 2020)
Background: In context of Nepal, although pregnant women from city areas contribute to maternal mortality, evidence of the study of utilization of antenatal care services and factors affecting antenatal care visits (ANC) are focused in rural areas where health institutions are not easily available. The objective of this study was to identify ANC services utilization by eligible women in Pokhara sub-metropolitan city. Methods: This was a cross-sectional study conducted applying face to face interviews with 240 eligible women bearing at least one youngest child below the age of two years. A structured and semi-structured questionnaire was used after translating into the Nepali language and pretesting it in the field. Data entered in Microsoft excel were transferred in SPSS (Statistical package for social sciences) version 21 and analysis were carried out. Both descriptive and inferential statistics were computed. The significance was set at the 0.05 level. Results: Approximately 97.0% of women had visited ANC during their recent pregnancy and about 56.0% of women had ≥4 ANC visits. The majority (80.3%) of the women used to seek ANC checkups during their first trimester and nearly half (49.0%) of the respondents belonged to the younger age of 15-19 years. Women’s (99.0%) and her husbands’ (86.0%) educational level significantly impacted ANC visits. Women having fewer numbers of children (98.0%) and the nuclear family (99.0%) had significantly higher ANC visits. Husbands’and mother-in-laws’ encouragement to go for ANC visits was significantly higher. All of the above-mentioned parameters were statistically significant at p< 0.05 level. Conclusions: There was variation in ANC service taking as per the encouragement from the husband and mother-in-law of the woman. Hence, awareness programs targeting husband and mother-in-law regarding the importance of ANC services are suggested. Conduction of detailed study in the future to explore the quality of services is recommended.